Efficient Swelling and Mercerization of Bagasse Fiber by Freeze-Thaw-Assisted Alkali Treatment - Cao, Liming; Zhu, Jiatian; Deng, Baojuan; Zeng, Fanyan; Wang, Shanshan; Ma, Yun; Qin, Chengrong; Yao, Shuangquan (Frontiers in Energy Research, 2022)
The mercerization of fiber is an important method for the high-value utilization of cellulose. In this study, the bagasse fiber was mercerized by freeze–thaw-assisted alkali treatment (FT/AT). The effects of freezing temperature, freezing time, alkali concentration, and thawing temperature on cellulose and hemicellulose removal were studied. The optimal freezing temperature was −40 °C, freezing time was 8.0 h, alkali concentration was 5.0%, and thawing temperature was 30 °C. The highest removal rate of hemicellulose was 75.64%. It was 5.80% higher than that of alkali treatment (AT). The alkaline degradation of cellulose was inhibited. The penetration of alkaline solution to fiber was promoted by the assistance of freeze-thaw pretreatment. The effective alkali concentration (5.0%) of cellulose I completely transformed into cellulose II decreased by 66.67% compared with traditional alkaline mercerization (15.0%). The high-efficiency mercerization of fiber was achieved by FT/AT. It provides theoretical support for promoting the high-value utilization of lignocellulosic biomass.